The Impact of Human Development Index and Population Number on Economic Growth in South Sumatra Province 2018-2022 - Sabardin; Shabur, Usman; Hidayat, Romi; Dly, Mhd Wildan Arif (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
This study aims to determine how the human development index and population affect economic growth in South Sumatra Province in 2018-2022. This study uses secondary data from the Central Statistics Agency (BPS) from 2018 to 2022. The Fix Effect Model (FEM) is the most appropriate model selection test found in this research approach, which uses a panel data regression analysis tool. The results of the study show that the HDI has a partial positive effect on economic growth, while the population has a negative effect that is not significant partially. Both variables simultaneously affect economic growth, emphasizing the role of the government in increasing population productivity to contribute to economic growth. In classifying a region as a Prosperous region, it is necessary to review the balanced Human Development Index (HDI) and population growth at a good level.